A New Mixed-Valence Mn(II)Mn(III) Compound With Catalase and Superoxide Dismutase Activities - Costa, Rafael O.; Ferreira, Sarah S.; Pereira, Crystiane A.; Harmer, Jeffrey R.; Noble, Christopher J.; Schenk, Gerhard; Franco, Roberto W. A.; Resende, Jackson A. L. C.; Comba, Peter; Roberts, Asha E.; Fernandes, Christiane; Horn Jr., Adolfo (Frontiers in Chemistry, 2018)
The synthesis, X-ray molecular structure, physico-chemical characterization and dual antioxidant activity (catalase and superoxide dismutase) of a new polymeric mixed valence Mn(III)Mn(II) complex, containing the ligand H2BPClNOL (N-(2-hydroxybenzyl)-N-(2-pyridylmethyl)[(3-chlorophenyl)(2-hydroxy)] propylamine) is described. The monomeric unit is composed of a dinuclear Mn(II)Mn(III) moiety, [Mn(III)(μ-HBPClNOL)(μ-BPClNOL)Mn(II)(Cl)](ClO4)2H2O, 1, in which the Mn ions are connected by two different bridging groups provided by two molecules of the ligand H2BPClNOL, a phenoxide and an alkoxide group. In the solid state, this mixed valence dinuclear unit is connected to its neighbors through chloro bridges. Magnetic measurements indicated the presence of ferromagnetic (J = +0.076(13) cm-1) and antiferromagnetic (J = -5.224(13) cm-1) interactions. The compound promotes O2• dismutation in aqueous solution (IC50 = 0.370 µmol dm-3, kcat = 3.6x106 M-1 s-1). EPR studies revealed that a high-valent Mn(III)-O-Mn(IV) species is involved in the superoxide dismutation catalytic cycle. Complex 1 shows catalase activity only in the presence of a base, e.g. piperazine or trimethylamine. The kinetic studies were carried out employing two different methods, resulting in kcat values of 0.58±0.03 s-1 (detection of O2 production employing a Clark electrode) and 2.59±0.12 s-1 (H2O2 consuption recorded via UV-Vis) . EPR and ESI-(+)-MS studies indicate that piperazine induces the oxidation of 1, resulting in the formation of the catalytically active Mn(III)-O-Mn(IV) species.